Biodiversity and Human Health Interlinkages in Higher Education Offerings: A First Global Overview - Cianfagna, Mark; Bolon, Isabelle; Babo Martins, Sara; Mumford, Elizabeth; Romanelli, Cristina; Deem, Sharon L.; Pettan-Brewer, Christina; Figueroa, Daniela; Velásquez, Juan Carlos Carrascal; Stroud, Cheryl; Lueddeke, George; Stoll, Beat; et al. (Frontiers in Public Health, 2021)
Introduction Biodiversity is inextricably linked to human health. As an important area of research of the Convention on Biological Diversity and a key avenue for the dissemination of biodiversity and health knowledge, we investigated how well embedded biodiversity and health interlinkages are in institutional higher education offerings. Methods Using One Health education programs as a starting point, we collected a global list of institutions potentially carrying out education in the links between biodiversity and health through previously published research, academic partners of global conglomerates, and our own networks. We then analyzed the offerings from these institutions to determine the degree of integration of biodiversity and health interlinkages. Results We found 105 educational offerings in biodiversity and health interlinkages from 89 institutions in 30 countries. These were primarily found in faculties of public health, veterinary sciences, and medicine, with varying degrees of coverage of the interlinkages. Conclusion Education incorporating the links between biodiversity and health exists globally, but should be more widely integrated, particularly through inter-faculty and inter-institutional collaboration.